2003
DOI: 10.1046/j.1365-2036.2003.01767.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of artichoke leaf extract in the treatment of patients with functional dyspepsia: a six‐week placebo‐controlled, double‐blind, multicentre trial

Abstract: SUMMARYBackground: This study aimed to assess the efficacy of artichoke leaf extract (ALE) in the treatment of patients with functional dyspepsia (FD). Methods: In a double-blind, randomized controlled trial (RCT), 247 patients with functional dyspepsia were recruited and treated with either a commercial ALE preparation (2 · 320 mg plant extract t.d.s.) or a placebo. The primary efficacy variable was the sum score of the patient's weekly rating of the overall change in dyspeptic symptoms (four-point scale). Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
1
12

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(77 citation statements)
references
References 19 publications
(14 reference statements)
0
64
1
12
Order By: Relevance
“…Artichoke leaf extract has been studied in a randomised placebo controlled trial for FD and a postmarketing surveillance study for IBS. 17,18 The extract improved global symptoms and quality of life (QOL) in dyspeptic patients when compared to placebo. The mechanism of action is not clear, but the extract has been shown to have antimicrobial effects, to stimulate bile flow, and may also act as an antispasmodic.…”
Section: Single Herb Therapymentioning
confidence: 99%
“…Artichoke leaf extract has been studied in a randomised placebo controlled trial for FD and a postmarketing surveillance study for IBS. 17,18 The extract improved global symptoms and quality of life (QOL) in dyspeptic patients when compared to placebo. The mechanism of action is not clear, but the extract has been shown to have antimicrobial effects, to stimulate bile flow, and may also act as an antispasmodic.…”
Section: Single Herb Therapymentioning
confidence: 99%
“…The individual studies all showed a substantial improvement of symptoms with Iberogast ® but varying results regarding its statistically significant superiority to placebo [57] . There are many other herbal medications used in the therapy of functional dyspepsia [59][60][61] . These include the traditional chinese herbal medicine Xinwei Decoction, ganaton (itorpide hydrochloride), capsaicin (red pepper) and artichoke leaf extract (ALE) [59][60][61] .…”
Section: Herbal Medicationsmentioning
confidence: 99%
“…There are many other herbal medications used in the therapy of functional dyspepsia [59][60][61] . These include the traditional chinese herbal medicine Xinwei Decoction, ganaton (itorpide hydrochloride), capsaicin (red pepper) and artichoke leaf extract (ALE) [59][60][61] . It is paradoxixal to consider red pepper as a potential therapy for FD, but capsaicin, through its desensitation of gastric nociceptive C-fibers may alleviate dyspeptic symptoms [61] .…”
Section: Herbal Medicationsmentioning
confidence: 99%
“…In general, the dried extract consisting of leaves and not flowering heads of artichoke has been eluted with water in European countries and the main components are caffeoylquinic acid derivatives (cynarin and chlorogenic acid), flavonoids (luteolin and apigenin) and bitters (cynaropicrin). [1][2][3][4] Artichoke leaf extract has been used for hepatoprotective 5,6) and cholesterol reducing 7,8) purposes. Based on in vitro 5,9,10) and in vivo 6,11) studies, it is believed that artichoke leaf extract is very effective as an antioxidant and its beneficial effects are attributed to its antioxidant action.…”
mentioning
confidence: 99%